EVALUASI KINERJA ALAT PENGOLAHAN SIRTU PT. BINTANG TIMUR LESTARI KOTA SORONG PROVINSI PAPUA BARAT - Chairun Nisa; Jance M. Supit (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
The processing of base course must be able to meet consumer demand. Thus, evaluating the works of the crushing plant as well as adjusting the final products by washing the sand. The problems state in this study are how much the pebble produce from the crushing plant, how much the pebble produce from the sand wash, what kind of obstacles during the process, and how to achieved better production. Further more the study aim to calculate the plant yield production; the diffraction yield is 3075,004 m3 / month with the distribution in each fraction of 3/8 (pebble) fraction of 381,175 m3 / month fraction 1 / 2 (gravel) of 853,121 m3 / month, fraction 2/3 (pebble) of 1164,484 m3 / month, and abubatu fraction of 676,424 m3 / month. The calculation results have not yet reached the company standard; fractions 3/8 (pebble) = 10%, fractions 1/2 (pebble) = 21%, and fractions 2/3 (gravel) = 29%, and rock ash fractions ( very fine sand) = 17%, with the desired presentation the company is a fraction 3/8 (pebble) = 5 - 10%, fraction 1/2 (pebble) = 20 - 25%, fraction 2/3 (gravel) = 30 - 35%, and rock ash fraction (very fine sand) = 20 - 25%. Hence, the results of the presentation are deficiencies in fractions 2/3 (gravel) and stone ash (very fine sand). Whereas for sand washing, the number of buckets is 1339 times per month, with the amount of volume entering 3385.97 m³ / month, and the total volume coming out is 3361 m³ / month. Constraints that occur in the processing process in this case during production such as improper working time, rain, repair of tools, and chunks larger than 35 cm.